MODEL PERILAKU PENCARIAN INFORMASI GUNA MEMENUHI KEBUTUHAN INFORMASI (Studi Literatur) - Nur Riani (Publication Library and Information Science, 2017)
The existence of information lately so abundant. This is in accordance with the needs of human information increasing. We can get information all over the place. Information can also be a useful information or useless. This is because many people had confusion about how find information as needed. As a seeker of information , must first be aware of the information needs which was continued by the search information stage. There are some characteristic search information according to Ellis, namely starting, chaining, browsing, differentiating, monitoring, extracting, verifying, and ending. Eisenberg dan Berkowitz also introduced stage search information that is famous for its Big Six Skills Model. Levels to begin with the definition of the task, search information strategy, the location and access, the use of information, synthesis, and evaluation. Stage or model search information about can be applied in the search information. Fulfill the need for give complacency , so are fulfill needs our information.